Effect of Aging on Muscle-Pump Baroreflex of Individual Leg Muscles During Standing - Verma, Ajay K.; Xu, Da; Garg, Amanmeet; Blaber, Andrew P.; Tavakolian, Kouhyar (Frontiers in Physiology, 2019)
Activation of leg muscles is an important component in the regulation of blood pressure during standing, failure of which could result in syncope and falls. Our previous work demonstrated baroreflex mediated activation of leg muscles (muscle-pump baroreflex) as an important factor in the regulation of blood pressure during standing; however, the effect of aging on the muscle-pump baroreflex of individual leg muscles during standing remains to be understood. Here, the interaction between systolic blood pressure (SBP) and the activation of lateral gastrocnemius (LG), medial gastrocnemius (MG), tibialis anterior (TA), and soleus (SOL) muscles during standing was quantified. Beat-to-beat heart period (RR interval), SBP, electromyography impulse (EMGimp) were derived from continuously acquired electrocardiography, finger blood pressure, and calf-electromyography, respectively. The cardiac baroreflex (SBP→RR) causality (0.88±0.08 vs 0.94±0.03, p=0.01), percent time with significant coherence (%SC: 50.95±23.31 vs 76.75±16.91, p=0.001), and gain (4.39±4.38 vs 13.06±8.11, p<0.001) was lower in older (69±4 years) compared to young (26±2 years) persons. Muscle-pump baroreflex (SBP→EMGimp) causality of LG (0.81±0.05 vs 0.88±0.08, p=0.01) and SOL (0.79±0.11 vs 0.88±0.04, p=0.01) muscles was lower in older compared to young persons. %SC was lower for all muscles in the older group (LG, p<0.001; MG, p=0.01; TA, p=0.01; and SOL, p<0.001) compared to young. The study outcomes highlighted impairment in muscle-pump baroreflex with age in addition to cardiac baroreflex. The findings of the study can assist in the development of an effective system for monitoring orthostatic tolerance via cardiac and muscle-pump baroreflexes to mitigate syncope and falls.